Cancer-mitochondria-targeted photodynamic therapy with supramolecular assembly of HA and a water soluble NIR cyanine dye. Issue 12 (26th October 2017) - Thomas, Ajesh P.; Palanikumar, L.; Jeena, M. T.; Kim, Kibeom; Ryu, Ja-Hyoung
Abstract : Herein, we introduce an indocyanine derivative (IR-Pyr ) that is highly water soluble, exhibiting higher mitochondrial targetability and better photostability than IR-780. Abstract : Mitochondria-targeted cancer therapies have proven to be more effective than other similar non-targeting techniques, especially in photodynamic therapy (PDT). Indocyanine dye derivatives, particularly IR-780, are widely known for their PDT utility. However, poor water solubility, dark toxicity, and photobleaching are limiting factors for these dyes, which otherwise show promise based on their good absorption in the near-infrared (NIR) region and mitochondria targeting ability. Herein, we introduce an indocyanine derivative (IR-Pyr ) that is highly water soluble, exhibiting higher mitochondrial targetability and better photostability than IR-780. Furthermore, electrostatic interactions between the positively chargedIR-Pyr and negatively charged hyaluronic acid (HA) were utilized to construct a micellar aggregate that is selective towards cancer cells. The cancer mitochondria-targeted strategy confirms high PDT efficacy as proved by in vitro and in vivo experiments.